Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fmicb.2022.972016
|View full text |Cite
|
Sign up to set email alerts
|

Minimal impacts on the wheat microbiome when Trichoderma gamsii T6085 is applied as a biocontrol agent to manage fusarium head blight disease

Abstract: Fusarium head blight (FHB) is a major fungal disease that causes severe yield and quality loss in wheat. Biological control can be integrated with other management strategies to control FHB. For this purpose, Trichoderma gamsii strain T6085 is a potential biocontrol agent to limit the infection of F. graminearum and F. culmorum in wheat. However, the possible impacts of T. gamsii T6085 on the broader microbiome associated with the wheat plant are not currently understood. Therefore, we identified bacteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…It can be assumed that an increase in biomass (although unfavorable from an economic point of view) indicates greater plant vigor and, consequently, plant health. Moreover, as evidenced by the previously cited literature reports [ 58 , 73 , 74 ], the effect of inoculation with Trichoderma fungi in field conditions could depend on weather conditions. According to locally monitored data (2017/2018 in Cerekwica, Western Poland; GPS coordinates: 52°5′ N, 16°7′ E), the temperature during the sowing of winter wheat Legenda in the second half of September 2017 was T max 17 °C and T min 13 °C, with precipitation of 3 mm.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…It can be assumed that an increase in biomass (although unfavorable from an economic point of view) indicates greater plant vigor and, consequently, plant health. Moreover, as evidenced by the previously cited literature reports [ 58 , 73 , 74 ], the effect of inoculation with Trichoderma fungi in field conditions could depend on weather conditions. According to locally monitored data (2017/2018 in Cerekwica, Western Poland; GPS coordinates: 52°5′ N, 16°7′ E), the temperature during the sowing of winter wheat Legenda in the second half of September 2017 was T max 17 °C and T min 13 °C, with precipitation of 3 mm.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have indicated that the effect of Trichoderma pre-inoculation is not stable over time and may depend on climatic conditions. Sarocco et al [ 73 ] and Alukumbura et al [ 74 ] described the variable effects of the pre-inoculation of T. gamsii T6085 wheat ears on the frequency and severity of FHB caused by F. graminearum and wheat agronomic parameters. Based on quantitative analysis, Alukumbura et al [ 74 ] noted that pre-inoculation with T. gamsii T6085 did not limit the abundance of F. graminearum in wheat ears/kernels, although disease rates were reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demonstrating the modulation of defence-related genes in wheat-both at localized and systemic level-not only when T6085 is inoculated alone but also when applied prior to infection with the pathogen, means this isolate can profit from all the mechanisms of action, direct and indirect, of a commercial biocontrol agent (Collinge et al, 2022). In light of these new results, it is possible to assert that the effect already observed under field conditions (Alukumbura et al, 2022;Sarrocco, 2023) in terms of disease control is due to the ability of T6085 to modulate a defence response in its plant host.…”
Section: Positive Effects Ofmentioning
confidence: 94%
“…Recently, the use of beneficial bacteria, yeasts and filamentous fungi has been reported to reduce FHB both in terms of disease control and prevention of mycotoxin contamination (Sarrocco, Mauro, et al, 2019), with endophytes actually considered as the last frontier in the management of FHB on cereals (Rojas et al, 2020). Within this context, the ability of Trichoderma gamsii T6085 to control FHB symptoms (Alukumbura et al, 2022;Vicente et al, 2020) and mycotoxin accumulation, coupled with mycoparasitic, antagonistic and competitive activities against Fusarium graminearum, one of the main causal agents of FHB on wheat, have been investigated for a long time (Matarese et al, 2012;Sarrocco et al, 2013;Sarrocco, Valenti, et al, 2019). The ability of this isolate to compete for cultural debris possession and to endophytically colonize wheat roots and spikes has been demonstrated (Sarrocco et al, 2013(Sarrocco et al, , 2021, while the plant response to T6085 colonization has not been fully investigated yet.…”
Section: Introductionmentioning
confidence: 99%